Transformasi Pengelolaan Keuangan Keluarga pada Sentra Industri Kerupuk Jabon: Pendampingan Berbasis Participatory Action Research - Dwi Susanto; Haris Shofiyuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Family financial planning assistance for the Kampung Kerupuk UKM in the Kedung Rejo Village, Jabon, Sidoarjo East Java aims to enhance the financial literacy skills of families, because the fact show that the majority of UKM actors don’t understand how to manage finances well so this has an impact on the welfare of the community, especially the family it self. The Research, entitled “Family Financial Planning Coaching in Kampung Kerupuk Kedung Rejo Village, uses a PAR approach with the aim of making village communities independent so they can understand and know, how to manage family finance. The research results show that financial planning assistance has a positive impact on family financial management abilities among UKM actors. The increased in understanding of financial planning, debt management and income diversification is proof of the effectiveness of the mentoring program.